Dynamic Structure Factor of Disordered Quantum Spin Ladders - Hörmann, Max; Wunderlich, Paul; Schmidt, Kai Phillip (Physical Review Letters, 2018)
We investigate the impact of quenched disorder on the zero-temperature dynamic structure factor of two leg quantum spin ladders. Using linked-cluster expansions and bond-operator mean-field theory, huge effects on individual quasiparticles but also on composite bound states arid two-quasiparticle continua are observed. This leads to intriguing quantum structures in dynamical conelation functions well observable in spectroscopic experiments.